Yupana y quipu para desarrollar estrategias de estimación y cálculo en Matemática en una Institución Educativa, Trujillo -2019 - Cruz Zavaleta, Jeny Raquel (2022)
The present investigation entitled “Yupana and quipu to develop estimation and calculation strategies in Mathematics in an Educational Institution, Trujillo – 2019”. this research is aimed to determine the influence of the use of “Yupana and quipu” in the development of strategies and calculation in mathematics in the students of the first grade of Primary Education of the Experimental Educational Center “Rafael Narváez Cadenillas”, Trujillo – 2019. In addition, the purpose was to improve in the students the development of the ability to use estimation and calculation strategies in mathematics through the use of “Yupana and quipu”. It was carried out with the population of 73 first grade students. The study sample consisted of 21 children from the control group and 25 children from the experimental group, who were given a devolvement test before and after applying the sequence of scheduled sessions on the use of “Yupana and quipu”. The experimental group, after applying the posttest, significantly improved the development of estimation and calculation strategies in mathematics, since we obtained the following results: before using “Yupana and quipu”, the majority of students were at the beginning (28.0%) and achieved (44.0%) levels and with an average score of 12. 24 points, after using “Yupana and quipu” the students were located at the achieved (28.0%) and satisfactory (72.0%) levels, but we did not find any student at the start and process level with and average score of 18.28 points.